Teacher evaluation and teacher professional development : two case studies of international language centers in Vietnam - Tran, Chi (2018)
Tran, Chi. 2018. Teacher Evaluation and Teacher professional development – Two case studies in an International Language Center in Vietnam. Master's Thesis in Education. University of Jyväskylä. Department of Education. The study is about teacher evaluation in an English language organisation who has a great number of small English language centres in some big cities in Vi-etnam. The purpose of the study is to find out the purpose of teacher evalua-tion, evaluation criteria, evaluation process, feedback and teachers’ comments about the whole evaluation process. The study also tries to find out whether there is a specific evaluation procedure in this particular organisation. If not, it is necessary to build up one complete and detailed procedure to use within this organisation in the future. The study consists of two case studies which data was collected by a semistructured interview in a face-to-face situation from two language centers belonging to the same international English langauge teaching organization. In each case study, a few teachers and their supervisor were interviewed. Partici-pants were chosen according to their availability and voluntary. The data was analysed using qualitative content analysis method and in mostly in deductive way. Six themes were developed from research questions, interview questions and literature review. Then if there were any new themes arisen, it would also be consolidated and discussed (Creswell, 2007). The study revealed that there were specific criteria and procedure in teacher evaluation in this organisation and it was applied consistently in both case studies. Teachers were happy with the evaluation process and they found it helpful in assisting them to become better teachers. Especially, when the purpose of the evaluation was professional development, the feedback was something teachers really appreciate to get. One new theme, the influence of educational leadership ppeared although the researcher did not address them directly in research questions or interview questions. This new theme was hid-den throughout the whole data, so it would not be presented as a subheading in Results chapter. Instead, it will be discussed in details in Discussion chapter, part 7.7. The study concluded that classroom observation or teacher evalua-tion was one of the main factors of an effective educational organisation ad-vancement (Marshall, Smart, & Alston, 2016; Martinez, Taut, & Schaaf, 2016; Rigby et al., 2017) . Maintaining high teaching quality was the key to success (Le, 2011). This study would be an example and needed to be considered for further research in the same topic within Vietnamese context.